2022
DOI: 10.1089/neu.2021.0401
|View full text |Cite
|
Sign up to set email alerts
|

Renin Angiotensin System as a Potential Treatment Target for Traumatic Brain Injury: A Systematic Review and Meta-Analysis

Abstract: Traumatic brain injury (TBI) is a major health concern and leading cause of death and disability in young adults in the UK and worldwide, however, there is a paucity of disease modifying therapies for the treatment of TBI. This review investigates the potential of the reninangiotensin system (RAS) as a treatment pathway for traumatic brain injury (TBI) in adults.Relevant electronic databases were searched on 18 December 2019, updated 16 May 2021. All English language articles with adult human or animal populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 93 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…Although this has historically been known as the RAS pathway, recent studies have shown that the pathway is more complicated and detailed than previously thought. 4 16 40) …”
Section: Local and Systemic Rasmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this has historically been known as the RAS pathway, recent studies have shown that the pathway is more complicated and detailed than previously thought. 4 16 40) …”
Section: Local and Systemic Rasmentioning
confidence: 99%
“…In addition to natural ligands, receptors can be activated or inhibited through pharmacological or genetic manipulation. 4 40) AT1R activation leads to neuroinflammation, the induction of oxidative stress, BBB disruption, and cell death. In contrast to AT1R, AT2R induces DNA repair and cell differentiation.…”
Section: Local and Systemic Rasmentioning
confidence: 99%
See 3 more Smart Citations